“His Main Problem Was Not Being in a Relationship With God”: Perceptions of Depression, Help-Seeking, and Treatment in Evangelical Christianity - Lloyd, Christopher E. M.; Mengistu, Brittney S.; Reid, Graham (Frontiers in Psychology, 2022)
Some Christian communities may understand mental illness as the result of spiritual causes, such as sin, demons, or a lack of faith. Such perceptions are likely to influence how Christian individuals conceptualise and experience their mental health and enact help-seeking behaviours. This study explores perceptions of depression and mental health help-seeking in evangelical Christianity by using a novel qualitative story completion task. A convenience sample of 110 Christian participants from the UK completed a third-person, fictional story stem featuring a male with depression who entered his local church. A contextualist-informed thematic analysis illustrated how the disclosure of depression was represented as eliciting negative social reactions, potentially rendering individuals with depression as socially dislocated. Stories suggested that, increasingly, evangelical Christians may perceive a spiritualisation of mental illness, which negates reference to psychological, social and biomedical representations, as unhelpful. Findings reveal the risks of a solely spiritual aetiology of depression and highlight how existing mental ill-health can be exacerbated if fundamentalist beliefs and approaches to therapeutic care are prioritised over holistic models of care. Methodologically, this study demonstrates the value of a rarely-used tool in psychology —the story completion task—for examining socio-cultural discourses and dominant meanings surrounding stigmatised topics or populations.